PENGARUH CURRENT RATIO, DEBT EQUITY RATIO, DEBT ASSET RATIO, DAN PERPUTARAN MODAL KERJA TERHADAP RETURN ON ASSET PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010 – 2012 - Alfarizi Cahya Utama; Dul Muid (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the factors that affect disclosure Return on Assets, namely: current ratio, debt equity ratio, debt-asset ratio and working capital turnover.The sample used is secondary data from the Indonesia Stock Exchange (IDX) Annual Report which manufacturing firms listed on the Indonesia Stock Exchange in 2010-2012. The samples were selected using purposive sampling methods and sample that meets the criteria. This study uses the classical assumption test, test the feasibility of the model, multiple regression analysis and statistical t test.These results indicate that the variable current ratio and debt equity ratio effect on return on assets, while the debt-asset ratio and variable working capital turnover showed no effect on return on assets.